Sin x*cos x-6sinx*cosx-6=0

sin x*cos x-6sinx*cosx-6=0 

    6tg^2(x)+5tgx-6=0

    t=(-5-13)/12            t=-3/2          tgx=-3/2        x=-arctg3/2+Пk,k принадлежит Z

    Пусть tg=x, тогда

    t=(-5+13)/12           t=2/3           tgx=2/3          x=arctg2/3+Пn,n принадлежит Z

    tgx-6tgx-6-6tg^2(x)=0

     

    D=25-4*6*(-6)=25+144=169

  • sin x*cos x-6sinx*cosx-6=0 

    6t^2+5t-6=0

  • 6sin(x-x)=0
    Sin(x-x)=0
  • sin x*cos x-6sinx*cosx-6cos^2(x)-6sin^2(x)=0|:(cos^2(x)) не равное 0

    S=arctg2/3+Пn;-arctg3/2+Пk

    или                         или             или               или


See also: